Green Bug Aphid Genome - McDowell, Connie; Scully, Erin (My University, 2017)
I studied the greenbug aphid (Shizaphis graminum), which has been recognized as a pest of grain crops and grasses for over 150 years and was first reported in North America in 1882 (University of Florida, Featured Creatures). In warm climates, most insects are female and they reproduce via parthenogenesis (Kansas State University, Sorghum Insects). Greenbugs are agriculturally important because they can feed on over 70 different species of plants. The basis for this project was to attempt to improve the greenbug aphid genome assembly using in order to better understanding its biology and why it have different host plants unlike other aphids. The question was, can we use sequencing data generated from 10X Chromium to improve scaffolding of the existing assembly? The results show that we did in fact improve the genome scaffolding using BWA and ARCS. These results are important because improving the genome allows us compare the greenbug genome to other aphids and measure gene expression (mRNA levels) as it feeds different plants to understand why it has such a broad host range.